Implementation of Improved Parameterization of Terrestrial Flux in WRF‐VPRM Improves the Simulation of Nighttime CO2 Peaks and a Daytime CO2 Band Ahead of a Cold Front. Issue 10 (14th May 2021) - Hu, Xiao‐Ming; Gourdji, Sharon M.; Davis, Kenneth J.; Wang, Qingyu; Zhang, Yao; Xue, Ming; Feng, Sha; Moore, Berrien; Crowell, Sean M. R.
Abstract: Enhanced CO2 mole fraction bands were often observed immediately ahead of cold front during the Atmospheric Carbon and Transport (ACT)‐America mission and their formation mechanism is undetermined. Improved understanding and correct simulation of these CO2 bands are needed for unbiased inverse CO2 flux estimation. Such CO2 bands are hypothesized to be related to nighttime CO2 respiration and investigated in this study using WRF‐VPRM, a weather‐biosphere‐online‐coupled model, in which the biogenic fluxes are handled by the Vegetation Photosynthesis and Respiration Model (VPRM). While the default VPRM satisfactorily parameterizes gross ecosystem exchange, its treatment of terrestrial respiration as a linear function of temperature was inadequate as respiration is a nonlinear function of temperature and also depends on the amount of biomass and soil wetness. An improved ecosystem respiration parameterization including enhanced vegetation index, a water stress factor, and a quadratic temperature dependence is incorporated into WRF‐VPRM and evaluated in a year‐long simulation before applied to the investigation of the frontal CO2 band on August 4, 2016. The evaluation shows that the modified WRF‐VPRM increases ecosystem respiration during the growing season, and improves model skill in reproducing nighttime near‐surface CO2 peaks. A nested‐domain WRF‐VPRM simulation is able to capture the main characteristics of the August 4 CO2 band and informs its formation mechanism. Nighttime terrestrial respiration leads to accumulation of near‐surface CO2 in the region. As the cold front carrying low‐CO2 air moves southeastward, and strong photosynthesis depletes CO2 further southeast of the front, a CO2 band develops immediately ahead of the front. Key Points: A new terrestrial ecosystem respiration parameterization is implemented in WRF‐VPRM to improve the simulation of both respiration and GPP The daytime bands of elevated CO2 mole fractions ahead of cold fronts form in part due to the accumulation of nighttime respiration Cloud shading induced perturbation of photosynthesis cannot explain the CO2 band immediately ahead of the surface cold front on August 4, 2016